DEVELOPMENT OF ANOXIA DURING THE HOLOCENE FRESH-BRACKISH WATER TRANSITION IN THE BALTIC SEA - Sohlenius G.; Emeis K.-C.; Andrén E.; Andrén T.; Kohly A. (My University, 2001)
One of the most pronounced environmental changes during the Holocene Baltic Sea history was the transition from the freshwater Ancylus Lake to the brackish water Litorina Sea. The establishment of brackish conditions during this transition (the A/L) was caused by an interplay of sea level rise and subsidence of sills in the Danish Straits. The northward progression of salt water influence caused the gradual and transgressive development of a halocline which obstructed vertical water circulation in the deep depositional basins. It caused changes in surface water properties (mirrored by diatom flora and productivity levels), in redox conditions of bottom waters, in organic carbon preservation of sediments, and in nutrient cycling. In seven cores from the Arkona, Bornholm and Gotland Basins, the A/L transition was 14C dated and studied in high-resolution samples for minor and major element composition.
Keywords: Holocene; anoxia; fresh–brackish water; Baltic Sea; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен